Reconstruction of post-burn scalp alopecia using tissue expansion in Erbil - Mustafa, Sabir Osman (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Reconstruction of post burn scalp alopecia using tissue expansion represents, nowadays, the standard method of treatment for this pathology. Tissue expansion is a straightforward technique, providing large skin flaps whose color and texture matches the area to be reconstructed, achieving optimal final aesthetic result. The aim of this study was to evaluate the results and complications of using tissue expansion for post burn scalp alopecia reconstruction. Methods: Thirty four patients having post burn scalp alopecia were treated with scalp tissue expansion, using forty tissue expanders at Rizgary Teaching Hospital in Erbil from February 2009 to December 2014. The age group ranged from 7-35 years and the mean age of the patients was 16 years. Statistical package for the social sciences (version 18) was used for data entry and analysis.Results: Complete reconstruction of post burn alopecia was achieved in 82.35% of the total patients with either a single or multiple sessions of expansions. The remaining 17.65% were benefited from reduction in the percentage of scar and recreation of anterior hair line. The size of scalp alopecia ranged between 4x7cm-11x20cm. Major complications occurred in 3 cases (8.8%), in which the expansion process was interrupted with removal of expander, while minor complications happened in 4 cases (11.76%), which did not interrupt the expansion. Conclusion: The use of tissue expansion for reconstruction of post burn alopecia is a useful and safe technique, since it is the only procedure that allows the development of normal hair bearing tissue to cover the areas of alopecia